การพัฒนาโมเดลเชิงสาเหตุของแรงจูงใจในการสอบและคะแนนสอบ ของนักเรียนมัธยมศึกษาปีที่ 3 - ประวีนา เอี่ยมยี่สุ่น (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objectives of this research were (1) to examine levels and compare the averages of test-taking motivation, levels of test scores of students under various test conditions; (2) to develop and validate a causal model of test-taking motivation and test scores; (3) to estimate direct and indirect effects of variables toward to test-taking motivation and test scores. The samples were 2,077 grade nine students. Samples were drawn from schools under the Office of the Sukhothai Educational Service Area, Surin, Ratchaburi and Phatthalung. The research instruments were: (1) the test-taking motivation scale and (2) the achievement test. Statistical analysises were conducted by using descriptive statistics, Pearson’s product moment correlation, and two-way ANOVA. The causal model analysis was employed using Mplus version 5.21. Major findings were as follow: 1. The averages of Thai language, and Mathematics test scores were moderate, low, respectively. The averages of test-taking motivation measured by rating scales was high, whereas the averages of test-taking motivation measured by scoring rubrics was good. It was also found that averages of test-taking motivation and test scores for autonomy support group were higher than non-autonomy support group. 2. The causal model of test-taking motivation and test scores was fitted to the empirical data. The model indicated that 1) Thai language subject - rating scales had X² = 152.315, df = 48, P =.000, CFI = .988, TLI = .978, RMSEA = .032, SRMR = .020; 2) Thai language subject - scoring rubrics had X² = 207.513, df = 59, P =.000, CFI = .971, TLI = .956, RMSEA = .035, SRMR = .026; 3) Mathematics-rating scales X² = 131.911, df = 49, P =.000, CFI = .992, TLI = .986, RMSEA = .029, SRMR = .023; and 4) Mathematics- scoring rubrics had X² = 134.791, df = 54, P = .000, CFI = .987, TLI = .978, RMSEA = .027, SRMR = .023. 3. Thai language test scores of students received the highest direct effect and total effect from test anxiety. Mathematics test scores of students received the highest direct effect and total effect from attitude towards Mathematics, and test-taking motivation of students received the highest direct effect and total effect from values of tests.